IMPROVING WRITTEN COMMUNICATION SKILLS IN MATHEMATICS LEARNING THROUGH PROBLEM-BASED LEARNING IN GRADE XII STUDENTS - Mitasari, Dewi; Noor Kholid, Muhammad; Anggoro Hermawan, Dwi (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2024)
Communication skills are one of the main skills that must be mastered in the 21st century, especially in learning mathematics. The ability to express ideas, situations, and events using mathematical language and symbols is important. The purpose of this study is to improve written communication skills in class XII students of SMA Batik 2 Surakarta through the implementation of Problem-Based Learning. The method used in this study was Classroom Action Research. The results show that the application of mathematics learning with a problem-based learning model helps improve written communication skills at SMA Batik 2 Surakarta. It can be shown that in cycle II (94%), 30 out of 32 students reached the completion of written communication skills. From these results, there was an increase compared to cycle I, which was 5 out of 32 students (16%). The average increase in test scores from cycle I to cycle II was 57%, from 51.41 to 80.78.